The Narrative of Pancasila as Indonesia's Moral Identity in Global Politics - Bahrul Ulum; Arsy Shakila Putri; Muhammad Zahran Agung Dewantoro; Imam Ragimov; Bernardus Agus Rukiyanto (Mahkota Science Publishers, 2025)
In a global political landscape increasingly defined by the battle of values, narrative power, and moral legitimacy, this study departs from the provocative philosophical premise that Pancasila is not merely an ideological legacy frozen in national rituals, but rather a moral identity that is only meaningful to the extent that it can intervene in injustice, reject dehumanisation, and guide Indonesia to produce a credible ethical position amid the global crises of technology, climate, and identity populism. This study uses a qualitative approach with an interpretive-critical case study design combined with discourse analysis and narrative analysis, as its main objective is to interpret the construction of meaning and moral legitimacy that works through language, symbols, and practices of Indonesian representation in global politics, so that it is not relevant to reduce it to quantitative measurements or linear cause-and-effect testing. The results indicate that the Pancasila narrative can be positioned as Indonesia's moral identity, serving a dual function: strengthening Indonesia's normative legitimacy in global politics while shaping citizens' ethical orientation in responding to value-laden cross-border issues. Pancasila is a deliberate narrative that can be operationalised through public messaging, curriculum, cultural diplomacy, and strategic communication, so that Pancasila is no longer understood as rhetorical legitimacy, but as a tool capable of changing the way citizens interpret patriotism, promoting technological ethics, and mobilising collective action for justice in global issues.